2017
DOI: 10.1007/s00253-017-8660-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture-based production of defective interfering particles for influenza antiviral therapy

Abstract: Defective interfering particles (DIPs) lack an essential portion of the virus genome, but retain signals for replication and packaging, and therefore, interfere with standard virus (STV) replication. Due to this property, DIPs can be potential antivirals. The influenza A virus DIP DI244, generated during propagation in chicken eggs, has been previously described as a potential candidate for influenza antiviral therapy. As a cell culture-based manufacturing process would be more suitable to fulfill large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Due to the ability of in vitro derived DIPs to interfere with replication of full virus particles and induce immune response, their potential application as antiviral and immunostimulatory agents has been studied extensively in recent years [ 12 14 ]. However, the biological role of DIPs emerging during in vivo infection is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ability of in vitro derived DIPs to interfere with replication of full virus particles and induce immune response, their potential application as antiviral and immunostimulatory agents has been studied extensively in recent years [ 12 14 ]. However, the biological role of DIPs emerging during in vivo infection is not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…If we cannot guarantee that a fast-growing virus will suppress growth of a slow-growing virus, then this strategy might be risky. For example, some have suggested using defective interfering particles (DIPs) as a possible method for blocking infections [51][52][53][54][55]. DIPs cannot replicate on their own, but have a high growth rate when fully-functioning virus is present.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that 244 DI (UUG) virus, which is obtained as a mixture of WT and 244 DI (UUG) viruses after UV-irradiation, can inhibit WT virus propagation. 20 To investigate whether the purely clonal 244 DI (UUG) virus also suppresses WT virus replication, MDCK cells were coinfected with 244 DI (UUG) and WT viruses and the virus titers determined at 48 hpi by plaque assay using MDCK cells. In these experiments, the MOI of WT virus was consistently set to 0.0001, whereas that of coinfected 244 DI (UUG) virus ranged from 0.001 to 1.…”
Section: Purely Clonal 244 DI (Uug) Virus Prevents Replication Of Wmentioning
confidence: 99%